Sampling Standardisation of Date Palm (Phoenix dactylifera L.) Leaflets as a Biomonitor of Metal Pollutants in Acid Environments - Al-Shayeb, S.M.; Seaward, M.R.D. (Asian Journal of Chemistry, 2010)
Sampling standardisation is a basic requirement for obtaining spatially and temporally reproducible comparable results. Date palm, Phoenix dactylif- era L., leaves showed to be suitable as a biomonitor for atmospheric metal pollution. Thus this work was undertaken to establish a standard sampling technique for the analysis of date palm leaves. The results showed that metal distribution in the date palm is related to the age of leaves. The metal content was investigated as a function of a leaflet's position along the rachis, and also of distribution within an individual leaflet.